2017
DOI: 10.1039/c7fo00801e
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of anthocyanins in blackberry juice by glutathione fortification

Abstract: Blackberry anthocyanins provide attractive color and antioxidant activity. However, anthocyanins degrade during juice processing and storage, so maintaining high anthocyanin concentrations in berry juices may lead to greater antioxidant and health benefits for the consumer. This study evaluated potential additives to stabilize anthocyanins during blackberry juice storage. The anthocyanin stabilizing agents used were: glutathione, galacturonic acid, diethylenetriaminepentaacetic acid and tannic acid, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
2
9
0
1
Order By: Relevance
“…On the other hand, AC co‐pigmented with MC + Q50 showed absorbance of 1.9684 and 0.3751 at the same wavelength before and after heating, respectively. These results suggested that the multiple ligands efficiently protected AC‐chromophore against color fading, which agrees with recent findings 26–28 . As shown in Table 2, linear regression analysis was applied to determine the rate of color fading and TRA degradation of each mixture.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, AC co‐pigmented with MC + Q50 showed absorbance of 1.9684 and 0.3751 at the same wavelength before and after heating, respectively. These results suggested that the multiple ligands efficiently protected AC‐chromophore against color fading, which agrees with recent findings 26–28 . As shown in Table 2, linear regression analysis was applied to determine the rate of color fading and TRA degradation of each mixture.…”
Section: Resultssupporting
confidence: 88%
“…These results suggested that the multiple ligands efficiently protected AC-chromophore against color fading, which agrees with recent findings. [26][27][28] As shown in Table 2, linear regression analysis was applied to determine the rate of color fading and TRA degradation of each mixture. The faded color followed first-order kinetics during the heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Significant quantities of anthocyanin remain in pomace, due to the low solubility anthocyanin in water and bonds with the cell wall. Anthocyanins are the main source of the attractive red and black colours of the fruits (Stebbins et al ., ). Today a large number of studies on pomace are carried out in order to isolate bioactive compounds suitable for use in the food industry (Struck et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Both vegetal and animal tissues contain antioxidant molecules that help reduce their oxidation decay, but the extent of their protection during processing or storage is limited. To overcome this problem, supplementation with exogenous antioxidants, such as glutathione, has been tested in several matrices [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%